High Energy Spin Physics 1991
DOI: 10.1007/978-3-642-86995-2_63
|View full text |Cite
|
Sign up to set email alerts
|

Structures in the Nucleon-Nucleon System

Abstract: The status of dibaryon resonances in I = 0 and I = I states is discussed together with new data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…It has also been found that there exist many simple relations between the A N 's for hadron production in reactions using different projectile-target combinations. E.g., comparingp(↑)+p(0) with p(↑)+p(0), we predicted [16] that there should be change of sign for π + and π − productions, which is confirmed by the E704 data [5,7]. Predictions for processes using polarized neutron or deutron targets have also been made [18].…”
Section: A N For π Productionsupporting
confidence: 57%
See 3 more Smart Citations
“…It has also been found that there exist many simple relations between the A N 's for hadron production in reactions using different projectile-target combinations. E.g., comparingp(↑)+p(0) with p(↑)+p(0), we predicted [16] that there should be change of sign for π + and π − productions, which is confirmed by the E704 data [5,7]. Predictions for processes using polarized neutron or deutron targets have also been made [18].…”
Section: A N For π Productionsupporting
confidence: 57%
“…Data on A N for hadron production at high energies is now available for p(↑) + [5,7], and π + p(↑) → π (or η) + X [8]. These data show the following characteristics:…”
Section: Characteristics Of the Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Striking left-right asymmetries (A N ) for hadron production in single-spin high-energy hadron-hadron collisions have been observed [1][2][3][4][5][6][7][8][9]. Significant effects have been seen in the projectile fragmentation region in experiments with transversely polarized proton beams [3][4][5][6][7][8][9] as well as in those with transversely polarized anti-proton beams [5,9]. Data are now available not only for pions [3][4][5][6]9] but also for η meson [8], for kaons [9] and for hyperon [7].…”
Section: Introductionmentioning
confidence: 99%